2022
DOI: 10.1371/journal.pone.0277111
|View full text |Cite
|
Sign up to set email alerts
|

Variation in aorta attenuation in contrast-enhanced CT and its implications for calcification thresholds

Abstract: Background CT contrast media improves vessel visualization but can also confound calcification measurements. We evaluated variance in aorta attenuation from varied contrast-enhancement scans, and quantified expected plaque detection errors when thresholding for calcification. Methods We measured aorta attenuation (AoHU) in central vessel regions from 10K abdominal CT scans and report AoHU relationships to contrast phase (non-contrast, arterial, venous, delayed), demographic variables (age, sex, weight), body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Our previous research has demonstrated strong relationships between coronary calcification scores and abdominal aortic calcification (MAC), specifically at the L3 and L4 levels 15 , 25 , 26 . Leveraging such evidence, we proposed the use of the MAC score to approximate coronary calcium measurement using computed tomography scans of the abdominal aorta 15 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous research has demonstrated strong relationships between coronary calcification scores and abdominal aortic calcification (MAC), specifically at the L3 and L4 levels 15 , 25 , 26 . Leveraging such evidence, we proposed the use of the MAC score to approximate coronary calcium measurement using computed tomography scans of the abdominal aorta 15 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A central aortic lumen zone was identified on each relevant CT slice between L1 and L4 and its mean pixel value was computed for reference. Aortic calcification was determined by a dynamic threshold: calcification was identified as morphologic regions having pixel values five standard deviations above the reference 15 , 23 , 25 . Figure 4 displays a visualization of calcification region and resulting MAC scores for a higher (c.) and lower risk (d.) RAMP participant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with atherosclerotic cardiovascular diseases (ASCVDs) such as peripheral arterial occlusive disease (PAOD), abdominal aortic aneurysm (AAA), and carotid arterial stenosis, only contrast-enhanced CTs are commonly available. The standard threshold of 130 HU cannot be used in contrast scans because the blood contrast attenuation exceeds this threshold [7]. Therefore, a method to calculate calcium scores on contrast-enhanced CT is needed for patients with ASCVDs [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%